THE EFFECT OF LECTURER PEDAGOGICAL COMPETENCE ON LEARNING MANAGEMENT: THE MEDIATING ROLE OF LEARNING INNOVATION - Yudha Prapantja; Ahmad Suryadi (Multidisciplinary Research Studies in Social Sciences, 2026)
Effective learning management is vital for higher education quality. This study examines the impact of lecturers’ pedagogical competence on learning management and the mediating role of learning innovation. A quantitative design was employed, analyzing data from 85 students at Universitas Muhammadiyah Jakarta using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results indicate that pedagogical competence has a positive and significant effect on learning management, underscoring its central role in instructional practice. Conversely, the mediating effect of learning innovation was statistically insignificant. These findings suggest that innovation alone, without a strong pedagogical foundation, does not independently improve learning effectiveness. The study concludes that institutions should prioritize the development of pedagogical competence as the primary determinant of effective learning systems, while treating innovation as a complementary factorKeywords: Pedagogical Competence, Learning Management, Learning Innovation, Higher Education